El Curial, un repte filològic i historicocultural. - FRANCÉS, ANTONI FERRANDO (Scripta, 2023)
The article is a chronicle of Antoni Ferrando's personal contacts, between 1980 and 2023, with scholars of the Catalan language, literature and culture of the 15th century and with historians of the Middle Ages in order to promote the study of Curial and Guelfa and its international diffusion.